A STUDY ABOUT THE HEALTH REFERENCE INFORMATION SYSTEM IN THE CASE OF NON SPECIALISTICS IN KENDARI CITY PRIMARY HEALTH CARE: INFORMATION SYSTEM - Sartini Risky; Azis Harun; Anry Hariadhin Depu (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background: I Implementation of a  reference information system will not work well when its implementation is not in accordance with the policy or guidelines. One of the problems in implementing the referral system is the health information system, in this case the referral guidelines and referral templates. Methods: This research uses qualitative method and it conducted the Kendari City Inpatient Primary health care form April 2020 to August 2020. The informants in the study were the Kendari branch of the health insurance officers, consisting of the Head of the Inpatient Community Health Center, the doctors of Inpatient Primary health care, the Head of Primary Benefit Guarantee and 4 referral patients in the Inpatient Primary health care. Data analysis of interview data used a NVIVO QSR application 12. Results: There is a conceptual linkage between the Reference Guidelines, Referral Procedures, and Reference Patterns with the concept of implementing the referral system Conclusion: There is a conceptual linkage between the Reference Guidelines, Referral Procedures, and Reference Patterns with the concept of implementing the referral system.